Analisis Beneish Ratio Index Untuk Mendeteksi Fraudulent Financial Reporting Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2016 - Indarti, Indarti (Kesatuan Press, 2019)
This study aims to determine the percentage of Banking in Indonesia Stock Exchange listed 2015-201 were classified as non manipulators and manipulators. The object of this study is all Banking companies listed in Indonesia Stock Exchange to publish audited financial statements for the financial year 2015 to 2016. The sampling technique is by using purposive sampling where the sample is determined based on certain criteria specified by the author and have limitations in terms of generalization , Methods of data collection using the method of documentation. Data analysze technique used is quantitative descriptive analysis using Beneish Ratio Index. The variable in this study is the Days' Sales In Receivables Index (dsri), Gross Margin Index (GMI), Asset Quality Index (AQI), Sales Growth Index (SGI), and Total Accruals To Total Assets Index (TATA). The research result is an index analysis showed that the ratio of 2 (two) or 7,41% of the company samples classified as Manipulators. Companies that belong to the category of companies Manipulators have indications commit fraud (fraud) to the presentation of financial statements. Ratio index analysis showed that 16 (sixteen) companies, or 59,26% of the company samples classified as Non Manipulators. Companies belonging to the company Non Manipulators do not have any indication of fraud (fraud) against the not categorize of financial statement presentation as well as the company Manipulators Non company entered in the class of Grey / Grey Company, this group amounted to 9 companies or 33,33 % of companies sampled